TELAAH ATAS PERATURAN DAERAH KABUPATEN GOWA NOMOR 09 TAHUN 2013 PERSPEKTIF HUKUM TATA NEGARA ISLAM - Liswan, Liswan; Bakri, Muammar (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2020)
The State of Indonesia is a state of law, based on the provisions of article I paragraph 3 of the 1945 Constitution of the Republic of Indonesia. Adhering to decentralization in the administration of government, as required by article 18 paragraph (1) of the Republic of Indonesia 1945 Constitution